2009
DOI: 10.1140/epjd/e2009-00220-8
|View full text |Cite
|
Sign up to set email alerts
|

State transfer in intrinsic decoherence spin channels

Abstract: Abstract. By analytically solving the master equation, we investigate quantum state transfer, creation and distribution of entanglement in the model of Milburn's intrinsic decoherence. Our results reveal that the ideal spin channels will be destroyed by the intrinsic decoherence environment, and the detrimental effects become severe as the decoherence rate γ and the spin chain length N increase. For infinite evolution time, both the state transfer fidelity and the concurrence of the created and distributed ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Limiting our discussion to chains of length N = 3 and N = 5 as likely candidates for a first experimental demonstration (and also for numerical tractability) has allowed us to obtain insight into important characteristics of such a protocol in the presence of realistic noise. Our conclusions will be equally relevant for longer chains, which are known to be even more susceptible to decoherence [37][38][39]. We have shown that directly meeting quantum error correction thresholds remains infeasible even if all spins possessed the exceptional coherence time of NV − centers.…”
mentioning
confidence: 74%
“…Limiting our discussion to chains of length N = 3 and N = 5 as likely candidates for a first experimental demonstration (and also for numerical tractability) has allowed us to obtain insight into important characteristics of such a protocol in the presence of realistic noise. Our conclusions will be equally relevant for longer chains, which are known to be even more susceptible to decoherence [37][38][39]. We have shown that directly meeting quantum error correction thresholds remains infeasible even if all spins possessed the exceptional coherence time of NV − centers.…”
mentioning
confidence: 74%
“…1 During the last decade, special attention has been paid for describing QST in spin networks. [2][3][4][5][6][7][8][9][10][11][12][13][14] Indeed, spin based communication protocols are one of the best candidates for scalable computing for two main reasons. 15 First, spin excitations delocalize in lattices owing to the interactions that naturally arise between neighboring sites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a natural candidate for implementing quantum information processing tasks such as quantum state transfer [43][44][45], the spin model remains people's research focus for many years. Recently, quantum discord in various spin models have been studied by a number of authors [46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%